Calculation of electromagnetic field from mobile phone induced in the pituitary gland of children head model - Stanković, Vladimir B; Jovanović, Dejan; Krstić, Dejan; Marković, Vera; Dunjić, Momir (Vojnosanitetski pregled, 2017)
Background/Aim. A mobile phone is a source of electromagnetic radiation located close to the head and consequently its intense use may cause harmful effects particularly in younger population. The aim of this study was to investigate the influence of electromagnetic field of the mobile phone on the pituitary gland of the child. Methods. In order to obtain the more accurate results for this research 3D realistic model of child's head whose size corresponds to an average child (7 years old) was created. Electric field distribution in child head model and values of Specific Absorption Rate (SAR) at the region of pituitary gland were determined. This study was performed for the frequencies of 900 MHz, 1800 MHz, and 2100 MHz, as the most commonly used in mobile communications. The special attention was dedicated to the values of the electric field and the values of the SAR in the pituitary gland. For all frequencies over 10 g and 1 g of tissue average SAR was calculated. The electric field distribution and values of average SAR for 10 g and 1 g trough the model of child's head were obtained by the using numerical calculation based on the Finite Integration Technique (FIT). Results. The largest value of electric field in the region of the pituitary gland was at the frequency of 900 MHz, as a consequence of the highest penetration depth. Lower values of the electric field in the region of the pituitary gland were at frequencies of 1,800 MHz and 2,100 MHz. The SAR in the pituitary gland decreased as the frequency increased as a direct consequence of lower penetration depth. Conclusion. The electric field strength from a mobile phone is higher than the value specified by standards for the maximum allowable exposure limits. The high values of the electric field are not only in the vicinity of a mobile phone but also in tissues and organs of the human head. Particular attention should be paid to the exposure of children to radiation of mobile phones. Smaller dimensions of children’s head and smaller thickness of tissues and organs have as a consequence greater penetration of electromagnetic waves
Keywords: cellular phone; electromagnetic fields; child; models; theoretical; pituitary hormones